The emergence of coordinative structures during offensive movement for goal-scoring in soccer - Shafizadeh, M.; Sproule, J.; Gray, S. (International Journal of Performance Analysis in Sport, 2013)
This study examined how offensive movements leading to goal-scoring opportunities emerge through coordinative actions between players in professional soccer. Twenty soccer clubs in the English Premier League were observed and analysed for 12 successive competitive Premier League matches each during the 2011-12 season. A coordinative structure was defined as the partnership between the player who delivered the assist pass and the goal scoring player. According to conditions of two players in the last action before a goal being scored four coordinative states were defined: Passer Standing-Receiver Standing; Passer Standing-Receiver Moving; Passer Moving-Receiver Standing; Passer Moving-Receiver Moving. The result of repeated-measures Analysis of Variance (F3, 57=1.94, p>0.05) showed that there was no significant difference between the occurrence of different coordinative states. The Markov chain model was used to examine the predictability of coordinative structure states in successive matches. We found a low transition probability and small transitional rate in each coordinative state. The results showed that the emergence of coordinative structure during offensive movements varies between EPL soccer clubs and it follows a stochastic process in successive matches. One implication of these findings for coaches is the need for varied tactics in attack through using different states of coordinative actions between players in order to increase goal-scoring opportunities.